How Deployments Affect the Capacity and Utilization of Army Treatment Facilities - Resnick, Adam C.; Jacobson, Mireille; Kadiyala, Srikanth; Eberhart, Nicole K.; Hosek, Susan D. (RAND Corporation, 2023)
The Army wished to understand whether the Army’s Force Generation (ARFORGEN) cycle created ebbs and flows in the ability of military treatment facilities to provide care and respond to changing family needs as soldiers and care providers deploy and return home. This study examines how the cycle affects capability and soldier health care utilization at Army military treatment facilities and how it affects family health care utilization.